STUDI DESKRIPTIF KUALITATIF : ANALISIS PERBANDINGAN ANTARA SISTEM PENDIDIKAN AMERIKA SERIKAT DAN INDONESIA - Susilo, Ahmad Dwi; Annisa, Cindy Ermintia; Azizah, Siti; Nurjayadi, Muktiningsih; Ridwan, Achmad (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Education is an important part of a person's life. Through education a person can gain knowledge about morals, science, character, and other things that are important for social and state life. Each country has its own standards in providing education to its citizens. The purpose of writing this article is to make a comparison between education standards in Indonesia and the United States, especially in the state of California. The research method used is literature research. This study looked at several previous research studies and the standards applied in the two countries. Data analysis was conducted using qualitative descriptive techniques. Education standards in Indonesia and the United States-California are different. This can be seen from the different standards and outcomes. In the curriculum, Indonesia has a centralized curriculum which at the basic education level consists of 10 subjects plus local content. Whereas in the United States the basic education curriculum prioritizes soft skills with 4 general subjects that are derived in the form of sub-subjects. However, both the United States-California and Indonesia try to implement the best education standards according to the capabilities of the citizens and the characteristics of each country.